A Case of Thalassemia-Hb S Disease in Jakarta - Iskandar Wahidijat; A. H. Markum; S. Moeslichan (Paediatrica Indonesiana, 1974)
The first Hb S (Hb S trait) inIndonesia, was found by Lie-InjoLuan Eng (1956) in Jakarta. Asfar as we know the case presentedin this paper, is the first patient withthalassemia-Hb S disease ever foundin the Indonesian literature.